A molecular laser-induced breakdown spectroscopy technique for the detection of nitrogen in water. Issue 3 (1st February 2022) - Ma, Shixiang; Guo, Lianbo; Dong, Daming
Abstract : Nitrogen in solution could be detected sensitively by using molecular laser-induced breakdown spectroscopy (LIBS). Abstract : Nitrogen (N) content is a significant indicator for evaluating eutrophication. However, the conventional methods, such as alkaline potassium persulfate digestion ultraviolet (UV) spectrophotometry and the Kjeldahl method, always require chemical reagents especially acid or alkaline solution for sample pretreatment. Laser-induced breakdown spectroscopy (LIBS), as an all element analysis technology, is also applied to the detection of N. However, the detection sensitivity for N is poor by conventional atomic LIBS. Therefore, we proposed molecular LIBS to determine N in water. The results showed that the detection sensitivity could be improved by about three orders of magnitude using molecular LIBS compared to atomic LIBS. Optimal limits of detection (LoDs) of 0.6 μg mL −1 in argon (Ar) gas and 1.5 μg mL −1 in helium (He) gas were obtained, respectively. The optimal limits of quantification (LoQs) were 1.98 μg mL −1 and 4.95 μg mL −1 in Ar gas and He gas, respectively. The results indicated that the LoQ of 1.98 μg mL −1 in Ar gas met the surface water environmental quality standards of China (2 μg mL −1 for N). Furthermore, real waters including tap water and river water were analyzed by molecular LIBS. Compared with UV spectrophotometry, the average standard deviation was 8.16%. The work demonstrated the feasibility of molecular LIBS to realize the reliable determination of N in water eutrophication. Molecular LIBS is a promising in situ method for the detection of N in solution.